2021
DOI: 10.1590/1809-4422asoc20190255r1vu2021l1ao
|View full text |Cite
|
Sign up to set email alerts
|

Step by step: a participatory action-research framework to improve social participation in coastal systems

Abstract: Social participation enriches decision-making and is considered a civil right in many democratic countries, despite remaining a challenge. This paper presents evidence and discusses the evolution of social participation in the Araçá Bay (Southeastern Brazil), as a result of participatory action-research. Over three years, a process of social mobilization and participatory environmental assessment and planning engaged local stakeholders and resulted in a sustainable development plan. Enhanced social participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…These processes are a fundamental step when breaking the traditional top-down mode of governing and building public policies or programs (Newig & Fritsch, 2009). These interactions must be designed so that attendees have room for knowledge exchange and for realizing the importance of participating in the co-construction process of policies (Kim et al, 2018) and to be protagonists in changing their local realities (Grilli et al, 2021), which brings specific challenges. Workshops have been a preferred approach to discuss policy, as the face-to-face interaction in a group sets a favorable scenario for deliberation (Robert, 2004), especially when facilitators provide a welcoming environment and equalize power imbalances among participants (Grilli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These processes are a fundamental step when breaking the traditional top-down mode of governing and building public policies or programs (Newig & Fritsch, 2009). These interactions must be designed so that attendees have room for knowledge exchange and for realizing the importance of participating in the co-construction process of policies (Kim et al, 2018) and to be protagonists in changing their local realities (Grilli et al, 2021), which brings specific challenges. Workshops have been a preferred approach to discuss policy, as the face-to-face interaction in a group sets a favorable scenario for deliberation (Robert, 2004), especially when facilitators provide a welcoming environment and equalize power imbalances among participants (Grilli et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…PAR prioritizes the participants-in this case the community members, in defining the research priorities, active participation in knowledge gathering and exchange; and analysis and reflection on knowledge gathered to facilitate practice change and/or increase agency (Walter, 2009). It has been applied in many settings, particularly involving marginalized groups in areas such as health care and resource management (Baum et al, 2006;Grilli et al, 2021). In Australia, it is increasingly being employed to facilitate active involvement of Traditional Owners in areas of land management (Walter, 2009;Mussehl et al, 2022).…”
Section: Water Justice and Participatory Action Researchmentioning
confidence: 99%
“…In addition, participation of stakeholders and civil society is essential (Forester, 1999), and has already received ample attention. For example, the PAR (participatory action-research) approach from Brazil demonstrated the high potential of early and active engagement of the community approaches in stakeholders and other management forums to rise from a low degree of social capital, mobilisation, and trust among themselves toward a better informed and engaged community, committed to the sustainability of Araçá Bay's ecosystem services and uses (Grilli et al, 2021). A sense of ownership, equalising power relationships, and enhancing social participation can boost and maintain the engagement needed for long-term participatory processes.…”
Section: Findings In Srocc and Recent Literaturementioning
confidence: 99%